Understanding the Work Dynamics of Generation Z: The Role of Burnout in the Relationship Between Workload, Organizational Support, and Turnover Intention in the Hospitality Sector in Bali, Indonesia - I Putu Adi Pajar Kusuma Dinata; I Gusti Ayu Agung Omika Dewi (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2026)
The hospitality industry in Bali has experienced significant growth and increasingly relies on young workers, particularly Generation Z employees. However, the dynamic work environment, high service demands, and intense workload often create psychological pressure that may lead to burnout and increase employees’ intention to leave their jobs. This study aims to analyze the influence of workload and organizational support on turnover intention with burnout as a mediating variable among Generation Z employees in the hotel and restaurant sector in Bali. This research employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to Generation Z employees working in the hospitality industry. The sampling technique used purposive sampling, and the data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with the assistance of SmartPLS software. The findings indicate that workload has a positive influence on burnout and turnover intention, while organizational support has a negative influence on both burnout and turnover intention. In addition, burnout was found to significantly influence turnover intention. The results also reveal that burnout mediates the relationship between workload and turnover intention, as well as between organizational support and turnover intention. These findings highlight the important role of balancing job demands and organizational resources in maintaining employees’ psychological well-being and reducing turnover intention. This study contributes to the development of the Job Demands–Resources (JD-R) theory by emphasizing the mediating role of burnout in explaining the relationship between workload, organizational support, and turnover intention among Generation Z employees. Practically, the findings suggest that organizations, particularly in the hospitality sector, should manage workload proportionally and strengthen organizational support to prevent burnout and improve employee retention.